Detection of Mayaro virus infections during a dengue outbreak in Mato Grosso, Brazil - Vieira, Carla Julia da Silva Pessoa; Silva, David José Ferreira da; Barreto, Eriana Serpa; Siqueira, Carlos Eduardo Hassegawa; Colombo, Tatiana Elias; Ozanic, Katia; Schmidt, Diane Johnson; Drumond, Betania Paiva; Mondini, Adriano [UNESP]; Nogueira, Mauricio Lacerda; Bronzoni, Roberta Vieira de Morais (Elsevier B.V., 2015)
Arboviruses are common agents of human febrile illness worldwide. In dengue-endemic areas illness due to other arboviruses have been misdiagnosed as dengue based only on clinical-epidemiological data. In this study we investigated the presence of Brazilian arboviruses in sera of 200 patients presenting acute febrile illness, during a dengue outbreak in Sinop, MT, Brazil. The results showed that 38 samples were positive to Dengue virus (DENV) type 1, two samples to DENV type 4, and six to Mayaro virus. These results indicate that arboviruses others than DENV are circulating in Sinop and the surrounding region, which are going undiagnosed. In addition, molecular and evolutionary analyses indicate that two MAYV genotypes are co-circulating in Mato Grosso, Brazil. Thus, a strong surveillance program must be implemented to evaluate and monitor the distribution and the true importance of non-dengue arboviruses in the etiology of acute febrile illnesses.
Keywords: Arboviruses; Febrile illness; RT-PCR